Pluronic F-68 Improves Root Growth of Recalcitrant Rice Cultivar Through Enhanced Auxin Biosynthesis - Andrew De-Xian Kok; Janna Ong-Abdullah; Amanda Shen-Yee Kong; Rogayah Sekeli; Chien-Yeong Wee; Swee-Hua Erin Lim; Wan-Hee Cheng; Jiun-Yan Loh; Kok-Song Lai (Tropical Life Sciences Research, 2025)
In plants, roots play a vital role in crop performance and yield that impact the agricultural productivity. Pluronic F-68 (PF-68) is a type of non-ionic surfactant that is typically utilised as a plant growth additive. There is a lack of studies on the impact of PF-68 on root growth. This work aims to assess the impacts of PF-68 on recalcitrant MR 219 rice root growth. Supplementation of 0.04% PF-68 enhanced the length (18.50%) and number of roots (15.87%) of MR 219 rice. The PF-68-treated MR 219 rice also showed a significant increment in sugar accumulation (1.73 mg/mL) and glutamate synthase activity (0.88 ?mol/g protein). Consistent with the root growth enhancement, MR 219 rice supplemented with PF-68 recorded an increase in transcription levels of Indole-3-Acetic Acid 23 (OsIAA23) (1.84-folds) and WUSCHEL-Related Homeobox 11 (OsWOX11) (2.00-folds). Moreover, the PF-68-treated MR 219 rice also exhibited an enhancement of indole acetic acid (IAA) concentrations (27.33 ng/g FW), further suggesting its role in auxin biosynthesis. Taken together, our study revealed that the introduction of PF-68 enhanced the root growth of MR 219 rice through improved sugar accumulation, glutamate synthase activity and auxin biosynthesis.